Management Challenges of a Rare Case of a High‐Grade T‐Cell Lymphoma of the Vulva in a Premenopausal HIV‐Infected Woman: A Case Report - John Lugata; Kristen Riley; Tecla Lyamuya; Baraka Shao; Aisha Mohamed; Elizabeth Skinner; Alex Mremi; Bariki Mchome (Clinical Case Reports)
ABSTRACT Primary vulvar lymphoma is an exceptionally rare malignancy, comprising less than 1% of all vulvar cancers and an even smaller fraction of extranodal non‐Hodgkin lymphomas. Among these, high‐grade T‐cell lymphoma is exceedingly uncommon, with limited cases reported in the literature. Immunocompromised states, particularly HIV infection, are known to predispose individuals to aggressive and atypical lymphoid malignancies. This case report presents a rare instance of T‐cell lymphoma of the vulva in a premenopausal woman, with the diagnosis confirmed through histopathological analysis of vulvar tissue. To the best of our knowledge, this is the first reported case of its kind in Tanzania. Case History: We report the rare case of a 46‐year‐old, P1L1, premenopausal woman living with HIV who presented with a rapidly enlarging, painful right vulvar mass with ulceration and foul discharge for 7 months. Pelvic examination revealed a large firm, friable mass with an ulcerated, erythematous surface involving the right labia majora, posterior fourchette, and perineum. She was also noted to have ipsilateral inguinal lymphadenopathy. A pelvic Magnetic Resonance Imaging (MRI) with and without IV contrast confirmed the presence of an ulcerated mass arising in the right labium measuring 6 × 2 cm. Prominent and enhancing bilateral inguinal‐femoral lymph nodes were identified, the largest noted in the right inguinal region, measuring 4 × 2 cm. The radiological findings were suggestive of a right labial ulcerative malignant mass with inguinal‐femoral lymphadenopathy. Staging investigations revealed localized disease without systemic involvement (Ann Arbor Stage II‐E). Histopathological evaluation confirmed high‐grade peripheral T‐cell lymphoma, with immunohistochemistry (IHC) analysis results indicating that the tumor cells were positive for CD38, CD43, CD56, CD57, CD2, and CD3 but negative for CD4, CD5, CD20, BCL2, and PAX5. The findings favored the diagnosis of a high‐grade T‐cell lymphoma of the vulva, most likely extranodal NK/T‐cell lymphoma. The patient was managed with combination chemotherapy Cyclophosphamide, Doxorubicin, Etoposide, Vincristine, and Prednisolone (CHOEP) protocol alongside continued antiretroviral therapy. She showed a favorable initial response with significant tumor regression and remains under close follow‐up.